Paulo Freire e a política de assistência social: diálogo necessário para o trabalho no CRAS - Silva, Graziele Garbin Moreira da (2020)
The subject matter “Contributions by Paulo Freire to CRAS’s social work” came from the need to qualify the work performed of the CRAS’s workers, by a methodological approaches coherent with the Social Assistance Policy. The main goal of this research is to identify what contributions Freire's thought can bring to social work at CRAS, separated into two specific goals: a) To explicit the extent to the CRAS’s policy documents can be benefit from Freire's thought and ; b) To define elements of Freire's thought that contribute to a social work aimed at social protagonism in the CRAS. To achieve these objectives, an exploratory qualitative approach was chosen, using the bibliographic research procedure. With the hypothesis about Freire's good contributions to CRAS, fundamentally with regard to providing elements that strengthen the idea of social work committed to social protagonism, this research covered the specific goals through the literature review focous to CRAS and the Paulo Freire. At first, the review was directed to the CRAS in the Public Policy of Social Assistance. The most used revision materials were the Organic Law on Social Assistance - Loas, the National Policy on Social Assistance - PNAS, the CRAS’s Technical Guidance book, and PAIF’s Technical Guidance books. In this moment, it was possible to identify the CRAS’s objectives and functions, as well as, the challenges related to the incipient construction of methodological approaches in the execution of CRAS’s work. The bibliographic review’s second stape focus on Freire's thought, based on a Freire’s exclusive books selection and also his commentators. In this revision step, it was possible to understand the scope of Freire's thought through his critique about the rights violation of the human condition, where instead of being the human becomes a thing, which hurts the human ontological vocation of To be More. It introduces the concept of the oppression’s system in our society and shows the mechanisms for thes oppressed’s liberation, which have been systematized into dialogue, awareness, problematization, criticality, engagement and fight. In this same effort of the bibliography’s review, it was identified the phases of the Paulo Freire Method, which provided materiality to Freire's thought. Then, this research’s results were integrated and interpreted through content analysis in the categories of ontological dimension; ethical and political dimension and; methodological dimension and intervention proposal. In the ontological dimension, Freire's contributes to understanding of the Social Assistance’s user and worker that were analyzed, as a historical, cultural subjects capable and vocated to social transformation towards To be More. In the ethical and political dimension, Freire's contributions were established in the conception of ethics focused on life, as being the maximum value and the necessary popular politicization. In the methodological dimension, it has integrated the Freire’s contributions into three proposals to use in the CRAS. At the end of this work, it was concluded that Freire's thought is compatible with the Social Assistance Policy and his contributions are pertinent and relevant to the social work performed at CRAS.